Behavioral Responses to Taxation: Cigarette Taxes and Food Stamp Take-Up - Kyle Rozema; Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2015)
This paper investigates a previously unexplored behavioral response to taxation: whether smokers compensate for higher cigarette taxes by enrolling in food stamps. First, we show theoretically that increases in cigarette taxes can induce food stamp take-up of non-enrolled, eligible smoking households. Then, we study the theoretical predictions empirically by exploiting between and within-household variation in food stamp enrollment from the Current Population Survey as well as data from the Consumer Expenditure Survey. The empirical evidence strongly supports the model predictions. Higher cigarette taxes increase the probability that low-income smoking households take-up food stamps.
Keywords: L66; H21; H23; H26; H71; I18; 330; cigarette taxes; food stamp take-up; tax pass-through rate; unintended consequences